Comparative analysis of luminescence Property of Tb3+and Er3+Activated Calcium Silicate Phosphor - Verma, Shailendra; Mishra, Anup; Bhuie, Manmeet; Singh, Nirbhay K (International Journal of Computer Sciences and Engineering, 2025)
The silicates of calcium are known for their thermal stability, high temperature strength, low thermal expansion, cheep residence and chemical inertness. Silicate phosphors are used for a fluorescent, a cathode-ray tube, a luminous body, a vacuum ultraviolet excitation light emitting element etc. Calcium Silicate acquires a higher luminous efficiency when it is doped with rare earth activated ions. In present work the silicate is prepared by combustion method at initiating temperature of 700-8000 C, using urea as a fuel and activated by Er3+ and Tb3+. The prepared CaSiO3:Er3+and CaSiO3:Tb3+ phosphor was characterized by X-ray diffract meter (XRD), scanning electron microscopy (SEM), energy dispersive x-ray spectroscopy (EDX), photoluminescence (PL) and thermo luminescence (TL). The chemical composition of the sintered phosphor was confirmed by EDX spectra, The PL spectra indicate that both phosphor exhibit bright green emission and with excellent colour stability. The PL broadness were typically observed in the range of 650-680 nm. The detail analysis of result it is observed the both compositions are promising green emitting phosphor for white light emitting diode (LED) application.